A novel ethanol gas sensor based on α-Bi2Mo3O12/Co3O4 nanotube-decorated particles. Issue 37 (8th June 2020) - Din, Salah Ud; Haq, Mahmood ul; Khatoon, Rabia; Chen, Xuehua; Li, Li; Zhang, Manjun; Zhu, Liping
Abstract : A novel composite based on α-Bi2 Mo3 O12 /Co3 O4 nanotube-decorated particles was successfully synthesized using a highly efficient and facile two step system using electrospinning and hydrothermal techniques. Abstract : A novel composite based on α-Bi2 Mo3 O12 /Co3 O4 nanotube-decorated particles was successfully synthesized using a highly efficient and facile two step system using electrospinning and hydrothermal techniques. The small size Co3 O4 nanoparticles were uniformly and hydrothermally developed on the electrospun α-Bi2 Mo3 O12 nanotubes. The pure α-Bi2 Mo3 O12 nanofibers and composite based on α-Bi2 Mo3 O12 /Co3 O4 were examined using X-ray powder diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS) and Brunauer–Emmett–Teller (BET) analyses. From the BET measurements, the composite based on α-Bi2 Mo3 O12 /Co3 O4 exhibits a large specific surface area of 54 m 2 g −1 with mesopore diameter ranges of 2–10 nm, which is mainly attributed to the remarkable and dominant enhancement in gas sensing as compared to that of the pure α-Bi2 Mo3 O12 nanofibers (38 m 2 g −1 ) and Co3 O4 nanoparticles (32 m 2 g −1 ), respectively. In this work, the novel composite based on α-Bi2 Mo3 O12 /Co3 O4 presented a high sensitivity of 30.25 with a quick response/recovery speed towards 100 ppm ethanol at an optimal working temperature of 170 °C, as compared to the pure α-Bi2 Mo3 O12 nanofibers and Co3 O4 nanoparticles, which display a sensitivity of 13.10 and 2.99 at an optimal working temperature of 220 °C and 280 °C. The sensing performance of the composite based on the α-Bi2 Mo3 O12 /Co3 O4 sensor exhibits a superior sensing performance towards ethanol, which might be owed to the enormous number of superficial oxygen species, the small size catalytic effect of the Co3 O4 nanoparticles and the interfacial effect formed between the n-type α-Bi2 Mo3 O12 and p-type Co3 O4 leading to a high charge carrier concentration. This is a novel investigation of a composite based on an α-Bi2 Mo3 O12 /Co3 O4 sensor in the gas sensing era, which might be of vital importance in applications in the advanced gas sensing field.